A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems. (11th March 2013) - Kennedy, Christina M.; Lonsdorf, Eric; Neel, Maile C.; Williams, Neal M.; Ricketts, Taylor H.; Winfree, Rachael; Bommarco, Riccardo; Brittain, Claire; Burley, Alana L.; Cariveau, Daniel; Carvalheiro, Luísa G.; Chacoff, Natacha P.; et al.
Abstract Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.